Antecedents Customer Engagement on Social Media and Its Consequence to Purchase Intention in the DKI Jakarta Hotel Industry: Uses & Gratification Theory Perspective - Isana Sri Christina Meranga (Proceeding of International Conference on Global Innovation and Trend in Economics, 2022)
Based on the Uses and Gratification theory, the purpose of this paper is to investigate the factors influencing customer engagement on social media and its impact on purchase intention in the DKI Jakarta hotel industry. As antecedents to customer engagement on Facebook, four motives are investigated: surveillance, social interaction, information sharing, and attraction. The questionnaires were distributed to a convenience sample of 200 hotel guests. Structural Equation Modeling was used to assess and analyze the data, and five hypotheses were tested. Surveillance, social interaction, information sharing, and attraction all have a positive effect on customer engagement in the social media context, according to the findings. Customer engagement influences purchase intent positively. In theory, this study contributes significantly to predicting behavioral intentions that may influence hotel industry recovery prospects. Practically, the study concludes that social media engagement with customers is critical for managers to reclaim and revitalize the market in the current and upcoming post-pandemic COVID-19 period, particularly in the context of the hotel industry.